2009
DOI: 10.1080/07347330902775590
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Networks and Depression of Women Suffering from Early-Stage Breast Cancer: A Case Control Study

Abstract: The aim of this study was to investigate the areas of depression, anxiety, and social support using the structural model of the social network. By comparing the networks of two samples of breast cancer sufferers and healthy control participants, it was possible to identify differences in their relationships, in the shape of the networks themselves, and in the levels of depression and anxiety. Women with breast cancer described smaller and denser networks, including mainly kins whereas the healthy women include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Social support is linked not only to the structure of the network but also to the patients' capacity to contact resources 11,31,47 and, as we also found, to their ability to use these resources. Those with self-confidence and reliable social networks knew when to call upon social support and were more likely to have social support available.…”
Section: Balancing Distance and Closenessmentioning
confidence: 63%
See 3 more Smart Citations
“…Social support is linked not only to the structure of the network but also to the patients' capacity to contact resources 11,31,47 and, as we also found, to their ability to use these resources. Those with self-confidence and reliable social networks knew when to call upon social support and were more likely to have social support available.…”
Section: Balancing Distance and Closenessmentioning
confidence: 63%
“…22 How the support is experienced is, among other things, influenced by the type of relationship and the setting in which the support is given. 11,13 Previous studies have reported that women with newly diagnosed breast cancer who had relationship problems or no confidants were more likely to develop depression and anxiety during the first 5 years after diagnosis. 23 Different types of social support are suggested as being valuable to cancer patients at different points in their disease and treatment.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…For example, survivors with lower social support experienced higher concurrent levels of depressive symptoms than their more socially supported counterparts (Gagliardi et al, 2009; Nausheen et al, 2009). Among breast and ovarian cancer survivors, lower social support at cancer diagnosis predicted the development of depression during the subsequent five years (Hipkins et al, 2004; Burgess et al, 2005).…”
mentioning
confidence: 99%